Design of a Proactive Occupational Safety Monitoring System at the Transhipment Point Area - Heru Prasetya; Emmy Pratiwi (Journal of Social Research, 2026)
Transshipment point maritime coal logistics involves high occupational safety risks due to dynamic sea conditions, continuous operations, and complex vessel-handling activities. Current monitoring practices primarily rely on CCTV systems for security purposes, limiting the real-time detection of unsafe acts and delaying corrective interventions, which contributes to recurring human-factor-related accidents. A gap remains between safety reporting mechanisms and real-time behavioral observation, indicating the need for proactive monitoring integration at the Bulk Sumatra site. This study designed a proactive occupational safety monitoring system to improve the early detection of unsafe acts and support decision-making in complex maritime operational environments. A qualitative case study approach was employed using observations, interviews, and document reviews conducted at a transshipment point. The collected data were analyzed using Root Cause Analysis (RCA), SWOT analysis (Internal Factor Analysis Summary [IFAS]–External Factor Analysis Summary [EFAS]), and Design Thinking to develop a user-centered monitoring framework. The findings revealed discrepancies between reported unsafe conditions and observed unsafe acts, highlighting the limitations of existing monitoring practices. CCTV systems were found to be underutilized for occupational safety purposes. The proposed system integrates risk-based camera placement, digital safety reporting, monitoring dashboards, risk classification, and structured follow-up mechanisms to enhance response effectiveness. The system design emphasizes early warning capabilities, faster supervisory intervention, and improved accountability across operational areas. The proposed model enhances safety visibility, accelerates risk mitigation, strengthens occupational safety controls, and supports improved safety performance in transshipment operations. This study contributes to the transition from reactive safety management toward proactive, risk-based decision-making within maritime coal logistics operations.